PULSE WAVE VELOCITY PROGRESSIONE OVER A 3.7 YEARS FOLLOW-UP: FOCUS ON URIC ACID. (June 2018) - Maloberti, A.; Vallerio, P.; D'Angelo, L.; Luongo, A.; Qalliu, E.; Milani, M.; Magni, G.; Zanoni, J.; Varrenti, M.; Giupponi, L.; Meani, P.; Montero, B. Lopez; et al.
Abstract : Objective: The role of Uric Acid (UA) on the arterial stiffness progression in prospective studies has been evaluated only in three studies. Our aim was to evaluate the role of UA as a possible determinants of the Pulse Wave Velocity (PWV) progression over a 3.7 ± 0.5 years follow-up period in hypertensive subjects. Design and method: We enrolled 431 consecutive hypertensive outpatients 18–80 aged, followed by the Hypertension Unit of St. Gerardo Hospital (Monza, Italy). At baseline anamnestic, Blood Pressure (BP) and laboratory data as well as PWV were assessed. PWV was performed again at follow-up. We analysed data separately for gender with hyperuricemia defined as a UA > 6 mg/dL for women and > 7 mg/dL for men Results: Baseline age was 53.2 ± 13.1years, 43% were female, Systolic and Diastolic BP 141.8/86.8 ± 17.5/10.8mmHg, UA 5.2 ± 1.4 mg/dL and PWV 8.5 ± 2.0m/s. At follow-up, despite better BP values (132.5/78.8 ± 17.4/10.7mmHg, p < 0.001), PWV increases to 9.15 ± 2.3m/s (p < 0.001) with mean deltaPWV of +0.56 ± 2.2m/s. 66 patients were hyperuricemic (15%) and when compared to normouricemic were older (58.3 ± 11.6 vs 52.3 ± 13.1, p < 0.001) with superimposable baseline and follow-up BP whit a higher PWV baseline and follow-up (9.1 ± 2.7 vs 8.4 ± 1.8 and 9.9 ± 3.2 vs 9.0 ± 2.1, p < 0.05). Despite this, similar deltaPWV were found (0.8 ± 3.4 vs 0.5 ± 1.9, p = ns). Hyperuricemic female (6.8%, 12 subjects) were older (63.1 ± 10.6 vs 53.1 ± 13.4, p < 0.001), with similar baseline and follow-up BP and, despite similar baseline PWV, a higher follow-up PWV (11.1 ± 2.5 vs 8.7 ± 2.2, p < 0.001) and deltaPWV (2.1 ± 3.5 vs 0.5 ± 1.9, p = 0.01). In males no differences were showed in arterial stiffness in hyperuricemic (21%, 54 subjects). UA correlate with age, sex and baseline and follow-up PWV (r = 0.13 and 0.19) in the whole population but not with deltaPWV. In females UA significantly correlate with age, follow-up PWV (r = 0.31) and deltaPWV (r = 0.26). Contrariwise in male no significant correlation were seen. At multivariate analysis UA were not a significant predictor of arterial stiffness, also for gender analysis. Conclusions: in HT, arterial stiffness showed some sign of correlation with UA particularly in women. Despite this it were not a significant predictor of arterial stiffness and its progression. A strong limitation of the present work is the low number of hyperuricemic female subjects.